Recent epidemiological trends in HCV-infection in Ukraine - T. N. Shevchenko; M. B. Shcherbіninа; S. A. Latsinska; T. V. Diklenko (Regulatory Mechanisms in Biosystems, 2017)
Today liver damage caused by Hepatitis C Virus (HCV) is widespread and included in the list of diseases of a social character. The aim of this research is to identify the peculiarities and summarize the epidemiological characteristics of HCV-infection in Ukraine, based on a retrospective analysis of detecting HCV based on antibodies, RNA and its genotyping, taking into account the sex and age of infected people in regions of Ukraine and particularly in Dniprо and Dnipropetrovs’k region. The research materials were provided by sampling the results of screening tests and qualitative detection of RNA-HCV genotyping (1a, 1b, 2 and 3). The survey involved 10,394 people from different regions of Ukraine (2014–2016). HCV-infection was detected in 3,436 of them, accounting on average for 32.5% of those surveyed. We analysed further 1,113 cases with positive RNA-HCV genotyping. Detection of infection by age periods was: 0–9 years old – 0.8%, 10–19 – 0.5%, 20–29 – 11%, 30–39 – 32%, 40–49 – 30%, 50–59 – 19.5%, 60–69 – 5.0% and 70–79 – 1.0%. 603 (54.2%) infected people belonged to genotype 1; 107 (9.6%) belonged to genotype 2; 403 (36.2%) belonged to genotype 3. Women were more frequently infected by genotype 1b, with increased percentage of 1ab; men often had genotype 3. 1,513 inhabitants of Dniprо and Dnipropetrovs’k region were sent to be tested for anti-HCV in 2011–2015. The percentage of positive anti-HCV showed a sharp increase from 28% to 64% over the observation period. Detection of HCV by age periods was: 0–9 years old – 0.9%, 10–19 – 1.5%, 20–29 – 9.5%, 30–39 – 27.6%, 40–49 – 27.8%, 50–59 – 23.2%, 60–69 – 8.8% and 70–79 – 0.7%. 1 genotype was identified in 262 (56.8%) infected patients among 461 HCV-infected, 38 (8.2%) had genotype 2, 61 (35%) had genotype 3. 2.6% were diagnosed 1ab. In both populations that were tested, the frequency of detection of HCV was similar among men and women. Gender differences in the spread of genotype 2 haven’t been identified. The disease HCV remains one of the urgent problems of public health in Ukraine.